L2 Willingness to Communicate and Perceived Accent Strength: A Qualitative Inquiry. Issue 2 (4th March 2017) - Zarrinabadi, Nourollah; Khodarahmi, Ensieh
Abstract: This study examined whether and how English as a foreign language (EFL) learners` perceptions towards their own and others` accent is liable to impact their second language (L2) willingness to communicate (WTC). The content analysis of interviews with 20 EFL learners showed that L2 WTC was amenable to their hegemonic attitudes towards native English accents. As many as four recurring themes arose from the interviews which showed how perceived accent strength can impact L2 WTC. These include: Accent-related stigmas, accent-based disruptiveness, aspiration for showing off one`s accent, and self-perceived communicative competence and self-confidence. The paper concludes by discussing the implications of the findings and outlining avenues for future research.